2018
DOI: 10.1158/1535-7163.mct-17-1267
|View full text |Cite
|
Sign up to set email alerts
|

The DNA-PK Inhibitor VX-984 Enhances the Radiosensitivity of Glioblastoma Cells Grown In Vitro and as Orthotopic Xenografts

Abstract: Radiotherapy is a primary treatment modality for glioblastomas (GBM). Because DNA-PKcs is a critical factor in the repair of radiation-induced double strand breaks (DSB), this study evaluated the potential of VX-984, a new DNA-PKcs inhibitor, to enhance the radiosensitivity of GBM cells. Treatment of the established GBM cell line U251 and the GBM stem-like cell (GSC) line NSC11 with VX-984 under conditions resulted in a concentration-dependent inhibition of radiation-induced DNA-PKcs phosphorylation. In a simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 40 publications
1
62
0
Order By: Relevance
“…More recently, a selective inhibitor of NHEJ, VX-984, that preferentially affects transformed cells was described [85]. Studies in glioblastoma cell lines and tumor-bearing mice showed that VX-984 enhances radiosensitivity of brain tumors [86]. Notably, VX-984 dose dependently inhibited radiation-induced DNA-PKcs phosphorylation and attenuated clonogenic survival [86].…”
Section: Radiation Sensitizers In Hnscc: Targeting Dna Repair Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, a selective inhibitor of NHEJ, VX-984, that preferentially affects transformed cells was described [85]. Studies in glioblastoma cell lines and tumor-bearing mice showed that VX-984 enhances radiosensitivity of brain tumors [86]. Notably, VX-984 dose dependently inhibited radiation-induced DNA-PKcs phosphorylation and attenuated clonogenic survival [86].…”
Section: Radiation Sensitizers In Hnscc: Targeting Dna Repair Pathwaysmentioning
confidence: 99%
“…Studies in glioblastoma cell lines and tumor-bearing mice showed that VX-984 enhances radiosensitivity of brain tumors [86]. Notably, VX-984 dose dependently inhibited radiation-induced DNA-PKcs phosphorylation and attenuated clonogenic survival [86]. The safety and tolerability of VXλ84 in combination with chemotherapy was assessed in participants with solid tumors in clinical trial NCT02644278.…”
Section: Radiation Sensitizers In Hnscc: Targeting Dna Repair Pathwaysmentioning
confidence: 99%
“…Thus, repair pathway modulation is a feasible strategy for sensitization to radiotherapy. This idea is further supported by the observation that inhibition of DNA-PK, which inhibits NHEJ, also increases the cytotoxicity of radiation [ 57 , 58 ].…”
Section: Radiation Therapy and Its Sensitizersmentioning
confidence: 92%
“…DNA-dependent protein kinase (DNA-PK) and PARP inhibitors also increase the cytotoxicity of radiation [ 17 , 57 , 58 , 59 , 60 ]. In the presence of PARP inhibitor, damage checkpoint activation in response to radiation exposure is significantly elevated [ 61 ], leading to efficient induction of cancer cell death through apoptosis.…”
Section: Radiation Therapy and Its Sensitizersmentioning
confidence: 99%
“…Furthermore, several compounds display mixed activity against DNA-PK, including caffeine [ 72 ], vanillin [ 45 ], and two compounds that are currently in clinical development and act against mTOR and DNA-PK, LY3023414 and CC-15 [ 58 , 59 ]. Newer generation specific DNA-PK compounds include VX-984 and M3814 that are now in clinical development [ 57 , 60 , 61 ]. Preliminary results indicate that VX-984 enhances radio-sensitivity of brain tumour xenografts and could help in management of glioblastoma cells [ 57 ].…”
Section: Targeting Individual Nhej Proteinsmentioning
confidence: 99%